In the aftermath of the adoption of the landmark Pandemic Accord: what are the strategic options for its effective implementation in Africa? - Olushayo Oluseun Olu; Henry Bosa Kyobe; Robert Lubajo; Amos Petu; Abdulmumini Usman; Sylvester Maleghemi; Francis Chisaka Kasolo (Globalization and Health)
Abstract Background Following three years of complex negotiations, the Intergovernmental Negotiating Body announced consensus among Member States on 16 April 2025, leading to the adoption of the Pandemic Accord at the Seventy-Eighth World Health Assembly on 19 May 2025. The accord aims to address the systemic inequities and failures exposed by the COVID-19 pandemic by enhancing early detection and rapid response capacities, promoting equitable access to pandemic-related health products, and ensuring sustainable financing for pandemic activities. This commentary highlights why the accord is of critical importance to Africa and describes the strategic options for its effective implementation on the continent. Main text Africa, with its unique pandemic vulnerabilities and weaknesses in global health security capacities, stands to gain the most from the Pandemic Accord. The continent faces challenges such as high-threat pathogens, weak health systems, political instability, and limited domestic financing. Additionally, Africa’s low capacity to influence global negotiations and fragmented public health governance complicates the implementation of global health agreements. To overcome these challenges, eleven priority recommendations are proposed, including joint analysis and domestication of the accord’s provisions, strong political commitment, better alignment of regional and global health security initiatives and public health organizations, leveraging digital technologies, prioritizing local manufacturing, and community engagement. Conclusion We urge African stakeholders to collaborate in ensuring the transformation of the accord from a global commitment into meaningful pandemic prevention and control action for the continent.